Improving the Performance of Satbinmas through the Development of Pam Swakarsa to Prevent the Increase of Theft in Malang City Polresta (Indonesian Journal of Police Studies, 2024)
Collected data suggests that there is a uearly increase of theft auto cases. As a part of the Police that focuses on prevention to maintain peace and order, further research is done on Malang Town Police’s People Guidance Department. Peace and order itself is a concept that refers to a situation where there are no disturbances to the tranquility of the people so they feel safe and agendas in the local or national level is assured to be done. To maintain said peace and order it is important to take pre-emptive steps on existing disturbances. In the territory of Malang Town Police Resort the crime with the highest number is Auto Theft, be it motorcycles or automobiles based on the data from the Criminal Investigation Department. To prevent and decrease the crime rate of Auto Theft in Malang Town a research is done on efforts that can be done to Enhance the performance of The People Guidance Deparment which will effect the coaching of Civil Security and ultimately influence the execution of preventive steps. The Analization to deepen the understanding on this research is done using The Mangement Thoery, SWOT Analization, and Performance Theory as well as certain concepts namely Civil Security, Peace and Order, as well as Auto Theft. Qualitative approach is used in this research coupled with Observation, Interview, and Document Studies as Data Collection Method. The accumulated data is then processed using reduction, serving, and triangulation verification. Collected data that has been processed suggests that some factors inhibit the performance of Malang Town Police People Guidance Department in decreasing the number of Auto Theft, be it from the lack of person, shortage of computers and transportation, nor external factors such as the inactivity of Civil Securities like Neighborhood Watch Systems on crowded and dangerous places. Based on that condition we can conclude that the increase of personel and tools are required to facilitate the People Guidance Departments work of maintaining peace and order to decrease the number of auto theft.
Keywords: Kamtibmas; curanmor; keamanan; swakarsa